Impact Of Mudharabah And Murabaha Financing On Real Sector Growth In Asean Developing Countries - Nurhaliza, Yudina; Sari, Dwi Novita; Maisyahrani, Maisyahrani; Nabila, Fuzna Bimin Hatin (LPPM ISNJ Bengkalis, 2024)
This research aims to analyze whether mudharabah and murabaha financing have an impact on maximizing real sector growth in Indonesia, Malaysia and Brunei Darussalam. The method used in this research is quantitative with a descriptive-associative approach. The data used in this research comes from secondary data and time series data obtained from the Financial Services Authority (FSA) Islamic banking statistics report, Indonesian economic and financial statistics report, Kuwait Finance House annual report, Malaysian economy in Figures 2022 report, report annual Islamic bank Brunei Darussalam, and the International Monetary Fund (IMF) report. This research uses panel data regression analysis. The research results show that partial mudharabah and murabaha financing does not impact real sector growth. Simultaneously, mudharabah and murabaha financing significantly impact real sector growth. This research provides a new contribution to scientific development, stating that mudharabah and murabaha financing do not impact real sector growth. Practically, this research proves that there must be improvements related to mudharabah and murabaha financing so that they can have an impact on real sector growth.